Rhinoviruses as Pathogens of the Lower Respiratory Tract - Nikolaos G Papadopoulos; Sebastian L Johnson (Canadian Respiratory Journal)
Rhinoviruses (RVs) are the most common upper respiratory pathogens, inducing the majority of common colds worldwide. RV-related morbidity, although significant cumulatively, has been considered trivial for the individual patient. However, recent strong epidemiological associations of RVs with asthma exacerbations, including severe episodes requiring hospitalization, indicate that RV infections can result in serious disease. Current evidence supports the possibility that RVs infect the lower airways, inducing a local inflammatory response. Such evidence suggests that the role of RVs in other lower respiratory diseases, such as pneumonia, bronchitis, bronchiolitis and cystic fibrosis, should be re-examined with polymerase chain reaction-based methodologies, which are considerably more sensitive than traditional, cell culture-based techniques. The mechanisms through which RVs induce lower airway disease are studied to understand the relative contributions of the epithelial, neurogenic and immune components in the antiviral response, and to permit the design and implementation of specific treatments.